2011
DOI: 10.1002/jmri.22660
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of renal perfusion: Comparison of arterial spin labeling and dynamic contrast‐enhanced MRI

Abstract: Purpose: To provide the first comparison of absolute renal perfusion obtained by arterial spin labeling (ASL) and separable compartment modeling of dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI). Moreover, we provide the first application of the dual bolus approach to quantitative DCE-MRI perfusion measurements in the kidney. Materials and Methods:Consecutive ASL and DCE-MRI acquisitions were performed on six rabbits on a 1.5 T MRI system. Gadolinium (Gd)-DTPA was administered in two separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 31 publications
(35 reference statements)
3
38
0
1
Order By: Relevance
“…A good repeatability of the perfusion measurements (reported as coefficient of variation, CV) was found over the cortex [29,32,33,34] (CV = 4-16%) and the whole kidney [33,34] (CV = 3-7%), while the data for the renal medulla are sparse [34]. A good correlation of the cortical renal blood flow (RBF) was found for ASL and DSC MRI [29,35] in healthy volunteers. Measurements in an animal model showed that the ASL seems to underestimate the perfusion as compared to RBF measurements performed with fluorescent microspheres [36].…”
Section: Renal Asl Mri In Healthy Volunteersmentioning
confidence: 99%
“…A good repeatability of the perfusion measurements (reported as coefficient of variation, CV) was found over the cortex [29,32,33,34] (CV = 4-16%) and the whole kidney [33,34] (CV = 3-7%), while the data for the renal medulla are sparse [34]. A good correlation of the cortical renal blood flow (RBF) was found for ASL and DSC MRI [29,35] in healthy volunteers. Measurements in an animal model showed that the ASL seems to underestimate the perfusion as compared to RBF measurements performed with fluorescent microspheres [36].…”
Section: Renal Asl Mri In Healthy Volunteersmentioning
confidence: 99%
“…ASL uses a radiofrequency (RF) pulse to magnetically label water protons in blood, so that they act as a diffusible tracer. Subtraction of the labelled images from control images allows perfusion maps to be quantified by fitting a kinetic model to the data [9]. In standard single-inversion time (TI) ASL techniques, a single inversion labelling pulse is applied, and a perfusion value is calculated using a simplified model which neglects variations in renal tissue T 1 and makes assumptions concerning the bolus arrival characteristics and blood T 1 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…7T), thus resulting in long longitudinal relaxation time (T 1 ) and, therefore, enhanced the sensitivity of ASL techniques. Concerning the ASL scheme strategy, it has been recently demonstrated that, despite modest inversion efficiency, 9 the pCASL approach 2 provides several advantages compared with the widely used pulsed FAIR 14 technique 10,11,13 for mouse kidney perfusion measurement. For the readout strategy, several options are offered, among them EPI (echo planar imaging), RARE (rapid acquisition with relaxation enhancement), TrueFISP (true fast imaging with steady state precession), GRASE (gradient and spin echo), 15 UFLARE (ultra fast low angle rate) 16 or even spiral imaging.…”
mentioning
confidence: 99%